Field Tests of Performance and Their Relationship to Age and Anthropometric Parameters in Adolescent Handball Players - Hammami, Mehrez; Hermassi, Souhail; Gaamouri, Nawel; Aloui, Gaith; Comfort, Paul; Shephard, Roy J.; Chelly, Mohamed Souhaiel (Frontiers in Physiology, 2019)
Handball performance is influenced by age, anthropometric characteristics, technical skills, tactical understanding, and physical abilities. The aims of this study were (i) to determine differences in anthropometric characteristics and physical performance between adolescent handball players across age categories, and (ii) to determine which anthropometric and maturity variables have the greatest relative importance in fitness for this sport. Seventy-nine male handball players drawn from a team in the elite Tunisian Handball league (U18 (n=10); U17 (n=12); U16 (n=17); U15 (n=18) and U14 (n=22)) volunteered for the investigation. Assessments included sprint performances; change in direction tests [T-half test and Illinois modified test]; jumping tests [squat jump; counter movement jump; countermovement jump with aimed arms; five-jump test]; medicine ball throwing; handgrip force; back extensor force and selected anthropometric measurements. The individual's age category affected all measurements, with U17 and U18 players showing larger body measurements and significantly better absolute results on all physical tests than U14, U15 and U16 contestants. Scores for the majority of physical performance tests were closely inter-correlated. We conclude that U17 and U18 players show significantly better absolute results than the younger players on all physical tests. Multiple linear regressions, using block-wise entry, indicate that age is the strongest predictor of jump and sprint performances. Several anthropometric characteristics, including body mass, standing height and lower limb length were closely correlated with performance test scores, but after allowing for age only body mass added to the prediction of jumping ability.